2014
DOI: 10.7162/s1809-97772013000200013
|View full text |Cite
|
Sign up to set email alerts
|

Sound pressure level in a municipal preschool

Abstract: Summary Aim: To evaluate the sound pressure level to which preschool students are exposed. Method: This was a prospective, quantitative, nonexperimental, and descriptive study. To achieve the aim of the study we used an audio dosimeter. The sound pressure level (SPL) measurements were obtained for 2 age based classrooms. Preschool I and II. The measurements were obtained over 4 days in 8-hour sessions, totaling 1920 minutes. Results: Compared with established standards, the SPL measured ranged from 40.6 dB (A)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Interviews with teachers concerning negative working conditions and stress factors showed that noise (73%) is the third strongest occupational risk [ 10 ]. Some objective noise measurements in nursery schools showed maximum equivalent sound pressure levels over 8 h (L eq8h ) of up to 90 dB (A) in particular for the supervision of children in playing sections [ 11 , 12 , 13 ]. The average L eq8h in nursery schools is in the range of medium intensity of 60–85 dB [ 1 , 8 , 9 , 14 , 15 ], which can typically trigger extra-auditory effects.…”
Section: Introductionmentioning
confidence: 99%
“…Interviews with teachers concerning negative working conditions and stress factors showed that noise (73%) is the third strongest occupational risk [ 10 ]. Some objective noise measurements in nursery schools showed maximum equivalent sound pressure levels over 8 h (L eq8h ) of up to 90 dB (A) in particular for the supervision of children in playing sections [ 11 , 12 , 13 ]. The average L eq8h in nursery schools is in the range of medium intensity of 60–85 dB [ 1 , 8 , 9 , 14 , 15 ], which can typically trigger extra-auditory effects.…”
Section: Introductionmentioning
confidence: 99%